The Usability of Elementary Arabic Learning Module (EALM) for Ugandan Adults Muallaf (UAM): A Descriptive Evaluation of General, Specific, and Overall Constructs - Kirembwe Rashid Abdul Hamed; Mohd Aderi Che Noh; Siti Rosilawati binti Ramlan; Sakinah binti Ahmad; Hayati binti Ismail; Sarifah Nurhanum binti Syed Sahuri; Hishomudin Ahmad; Noor Azizi Ismail; Adibah Sulaiman @ Mohamad; Mardhiah Binti Yahaya; Mohammad Najib Jaffar (Penerbit USIM, 2024)
Al-Azkiyaa - International Journal of Language and Education Vol. 2 No. 2 (page: 134–154)